The influence of the metacarpophalangeal joint angle on the transversal area and mean echogenicity of the superficial digital flexor tendon and suspensory ligament in gaited horses - Schade J.* (2021)
© 2021 Japanese Society of Equine Science.The objective of this study was to assess the influence of the metacarpophalangeal (MCP) joint angle on the transversal area (TA) and mean echogenicity (ME) of the superficial digital flexor tendon (SDFT) and suspensory ligament (SL) in gaited horses. Ultrasound images were obtained from 50 healthy adult horses of the Mangalarga Marchador (MM; n=25) and Campeiro (n=25) breeds. Static and dynamic angles of the MCP joint were measured from photographs and video recordings. Higher ME values were evinced for the SL only in the group with the smaller dynamic angles of the MCP joint in the MM horses, in addition to weak negative correlation between the dynamic angle and ME. Moreover, weak negative correlation was also observed between the static angle and TA of the lateral branch of the SL and between the static angle and the ME of the SDFT. However, the difference observed in the group of MM horses, as well as the weak correlation, was not considered sufficient to support the hypothesis that a smaller angle of the MCP joint (greater extension) is associated with larger TA and ME values for the structures. The results also suggest that the static and dynamic angles of the MCP joint do not influence the TA and ME values of the SDFT and SL in gaited horses.